Arabic language learning reconstruction as a response to strengthen Al-Islam studies at higher education - Mahyudin Ritonga; Hendro Widodo; Munirah Munirah; Talqis Nurdianto (Institute of Advanced Engineering and Science, 2021)
Knowledge of the Islam at every student is supported by many factors, one of which is the Arabic language compentence. This research aimed to evaluate and find Arabic language learning construction in strengthening al-Islam at higher education. The desire to find the construction is because there is no visible connection between Arabic language learning and al-Islam learning so that clarity of learning objectives, learning materials, learning implementation, and evaluation systems of Arabic language learning at higher education is needed. In line with this purpose, this study used a qualitative method with a phenomenological approach. The sources of data were facts, Arabic language lecturers, al-Islam lecturers, and students purposively. Data were analyzed by using critical realism. The results of the study proved that the reconstruction of learning objectives, materials, implementation, and evaluation systems is needed to realize Arabic language learning that can strengthen al-Islam at higer education.